A Study Regarding Spanish-Speaking Parents' Preference of Physician Attire in the Pediatric Emergency Room. (July 2013) - Nibhanipudi, Kumara V.; Mason, Ben; Pandey, Akash; Henriquez, Roger; Hassen, Getaw W.
Objective . A study to determine Spanish-speaking parents' acceptance of the physician's attire in the pediatric emergency department. Hypothesis . The attire of the physicians does not matter for the parents. Methods and materials . The sample size was 450. An anonymous patient survey with no identifiers was used. The sample questionnaire was enclosed, and the parents were asked to answer the questionnaire. The results were interesting; patients preferred physicians who wear hospital scrubs (410/450 or 91%) and short hair (430/450 = 96%). They preferred physicians wearing sneakers (430/450 = 96%) compared with dress shoes, and male physicians with moustaches/beards and wearing glasses (450/450 = 100%). Parents did not like women physicians wearing makeup and high heels. Conclusions . Parents prefer physicians wearing hospital scrubs and sneakers and having short hair. This could indicate that parents do not prefer formal attire in the pediatric emergency room (ER). Also, a gender difference was noticed. Parents do not prefer women physicians with high heels and make up. But, they tolerate male physicians with moustaches/beards. This could be related to the fact that most of the parent questionnaires were answered by Spanish women. Results are interesting and useful in addressing the question of physicians' attire in the pediatric ER in the context of a predominantly Spanish speaking population.